The Last Mile: Using Local Knowledge to Identify Barriers to Sustainable Grain Legume Production - Smith, Barbara M.; Gathorne-Hardy, Alfred; Chatterjee, Soumik; Basu, Parthiba (Frontiers in Ecology and Evolution, 2018)
Leguminous species, and especially pulses (annual leguminous crops that are harvested solely for their dried seeds as a food), have an important yet under-appreciated role in sustainable cropping systems. Pulses contribute positively to soil fertility and agricultural biodiversity, and are a highly nutritious food source. Yet in India, soon to be the world’s most populous country, and the world’s largest importer, producer and consumer of pulses, pulses remain the only major food group not to have increased in output since independence in 1947. Given the multiple benefits of legumes it surprising that they are not grown more extensively and successfully by smallholders. Existing efforts to address this issue have focused on the scientific and agronomic barriers to increasing legume production. In contrast, this project focuses on the barriers to production as identified by the growers themselves. Working with 440 farmers from 19 non-tribal and 11 tribal villages in Tripura, NE India, we used facilitated discussion to identify their key barriers to pulse production. To identify the commonly consumed, grown and available pulses we used facilitated pile sorting. Twenty-eight barriers to legume production were identified by farmers, including eight principal barriers: water management; soil fertility; seed supply; lack of technical knowledge; financial constraints; limited fertiliser supply; lack of processing units and fencing. Understanding the wider socio-economic pathways to sustainable pulse production is essential to facilitate increased pulse production on the ground. Our results clearly demonstrated that a systems approach should be taken to the production gap of pulses